Prevalence of patent ductus arteriosus in premature infants at the Neonatal Ward, Cipto Mangunkusumo Hospital, Jakarta - Benita Deselina; Sukman Tulus Putra; Rulina Suradi (Paediatrica Indonesiana, 2004)
Background Patent ductus arterious (PDA) is one of the mostcommon congenital heart diseases encountered in preterm infants.The lower the birth weight and gestational age are, the higher theincidence of PDA is.Objectives To investigate the incidence of PDA in premature infantshospitalized in the neonatal wards of Cipto Mangunkusumo Hospitalusing echocardiography.Methods Preterm infants born between August and October 2003were included in this study. Clinical features were retrieved from medicalcharts. The first echocardiography was conducted on all of the preterminfants at the chronological age of 3 days. If PDA was detected,echocardiography was repeated at the chronological age of 6 days.Results During the 3-month period, sixty-five preterm infantsparticipated in this study and underwent echocardiography. In thefirst echocardiogram, the incidence rate of PDA was 32%. Atgestational age of less than 28 weeks, 1 of 2 infants had PDA. Of 3infants with birth weight of more than 1000 grams, 2 had PDA. Onthe second echocardiography, the incidence rate of PDA was 14%and mostly found in infants at gestational age of less than 28 weeks(8/9) and in those with birth weight of less than 1000 grams (7/9).All infants with RDS whose PDA was identified in the firstechocardiography proved to maintain their PDA in the secondechocardiography.Conclusion The incidence rate of PDA in preterm infants was14%. The lower the birth weight, the higher the incidence rate ofPDA. The presence of RDS is related to the delay in the closing ofthe arterial duct